Oligosaccharides Affect Performance and Gut Development of Broiler Chickens - Ao, Z. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2013)
The effects of oligosaccharide supplementation on the growth performance, flock uniformity and GIT development of broiler chickens were investigated. Four diets, one negative control, one positive control supplemented with zinc-bacitracin, and two test diets supplemented with mannoligosaccharide (MOS) and fructooligosaccharide (FOS), were used for the experiment. Birds given MOS or FOS had improved body weight (BW) and feed efficiency (FCR), compared to those fed the negative control diet during the 35-d trial period. The effect on FCR became less apparent when the birds got older. FOS and MOS supplementation reduced the pancreas weight as a percentage of BW, with an effect similar to that of the antibiotic, at 35 d of age. Birds given MOS tended to have a heavier bursa (p = 0.164) and lower spleen/bursa weight ratio (p = 0.102) at 35 d of age. MOS and Zn-bacitracin showed a clear improvement on flock uniformity, compared to FOS. The mortality rate was not affected by FOS or MOS.